Answer:
5x^2 - 13x + 6
Explanation:
(8x^2 - 6x + 2) - (3x^2 + 7x - 4) =
First, drop the first set of parentheses because they are unnecessary.
= 8x^2 - 6x + 2 - (3x^2 + 7x - 4)
Now, distribute the minus sign to the left of the set of parentheses. Think of that negative sign as -1 multiplied by the parentheses. You change every sign inside the parentheses.
= 8x^2 - 6x + 2 - 3x^2 - 7x + 4
Next, group like terms together.
= 8x^2 - 3x^2 - 6x - 7x + 2 + 4
Finally, combine like terms.
= 5x^2 - 13x + 6